Diversity and distribution of wild mushrooms in different forest areas of Bankura district, WB, India - Ganguly, Arindam; Nad, Susmita; Singha, Krishanu; Pathak, Rituparna; Hazra, Palash; Singha, Pritha; Dhua, Priti; Mohapatra, Pradeep Kumar Das; Mandal, Asish (Acta Biologica Szegediensis, 2022)
Mushrooms are macroscopic fruit bodies of fungi; one of the most diverse groups of living organisms distributed all over the world. In recent past, they have gained significant scientific attention for their profound nutraceutical potentiality. The objective of the present study was to explore the diversity and ecological distribution of mushrooms in different forest areas of Bankura district. The study area includes intermittent dense forest and flood plains from middle-east to eastern part of Bankura district. However, this area received very little attention from a conservation perspective, and there is no such documentation on mushrooms of this area. The survey was conducted from August 2019 to October 2020 including vivid field surveys in the forest depots. The study has revealed a total of 53 identified mushroom species belonging to 40 genera and 30 families. The study has also identified 25 edible, 18 inedible and 15 medicinally potential mushrooms. The genus Russula and the family Russulaceae dominates the myco-population. The finding shows that this region is rich in macrofungal diversity complicatedly linked to the functioning of the local ecosystem. The present study opens new possibilities regarding the exploration and utilization of wild mushrooms in India.